Revolution in PAI Learning: Teacher and Parent Synergy With a Contextual Approach and Digital Communication to Improve Learning Motivation at SMPN 2 Bungo - Nadia Ananda Agustina; Sriani; Mabruri (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character, yet motivation to learn in this subject is often suboptimal, especially at the junior high school level. Synergy between teachers and parents in supporting religious learning at school and at home is key to improving student motivation. This study aims to explore how collaboration between teachers and parents can influence students' motivation to learn Islamic Religious Education at SMPN 2 Bungo. This study used a qualitative approach with a case study design, collecting data through interviews, observations, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques using the Miles and Huberman analysis model. The results show that intensive and ongoing communication between teachers and parents, both through regular meetings and WhatsApp groups, strengthens parental involvement in supporting students' academic and spiritual development. Furthermore, the application of a contextual approach in Islamic Religious Education learning by teachers increases the relevance of the material to students' lives, encouraging higher learning motivation. These findings provide an important contribution to understanding the importance of synergy between schools and families in religious learning. Implications of this study emphasize the need for policies that encourage parental and teacher involvement in religious education, as well as the use of technology to facilitate effective communication. Further research is recommended to expand the scope and triangulation methods to deepen understanding of this phenomenon.